2005
DOI: 10.1007/s10396-005-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatocellular carcinoma capsule by contrast-enhanced ultrasound using Levovist: correlations with pathological findings

Abstract: The arterial phase of CEUS is very useful for detection of HCC capsules and therefore facilitates selection of the most appropriate treatment method for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A lesion with fat degeneration shows poor and inhomogeneous enhancement within the adipose portions of the mass (clearly hyperechoic on baseline sonography) and relevant enhancement of the remaining tumor tissue (hypoechoic on baseline imaging). Bhattacharjee et al 35 found the neither enhancement nor the wash‐out pattern correlated with the presence of a capsule. The arterial phase of contrast‐enhanced sonography is very useful for detection of hepatocellular carcinoma capsules.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A lesion with fat degeneration shows poor and inhomogeneous enhancement within the adipose portions of the mass (clearly hyperechoic on baseline sonography) and relevant enhancement of the remaining tumor tissue (hypoechoic on baseline imaging). Bhattacharjee et al 35 found the neither enhancement nor the wash‐out pattern correlated with the presence of a capsule. The arterial phase of contrast‐enhanced sonography is very useful for detection of hepatocellular carcinoma capsules.…”
Section: Discussionmentioning
confidence: 98%
“…With the development of second generation sonographic contrast agents and contrast‐specific imaging techniques, real‐time contrast‐enhanced sonography can be used to visualize lesion perfusion. Contrast‐enhanced sonography has become a useful and less invasive method for characterizing and evaluating the intranodular blood supply of focal liver lesions, and it can indicate pathologic features of hepatocellular carcinomas preoperatively 35 37 …”
Section: Discussionmentioning
confidence: 99%